The social legitimacy of disability inclusive human resource practices: the case of a large retail organisation. (21st November 2017) - Moore, Katherine; McDonald, Paula; Bartlett, Jennifer
Abstract : Research in the field of HRM has begun to examine organisational responses to social policies around welfare‐to‐work programs. However, relatively little research has examined how organisations respond to the increased demand from people with disability for employment opportunities. The current study addressed this knowledge gap by exploring how a large Australian retail organisation legitimises disability employment practices against the background of the institutional context of disability employment. The findings revealed that the organisation seeks social legitimacy for disability employment practices primarily based on social expectations and to a lesser extent, from government funded disability employment agencies. The study makes three important contributions to the SHRM literature. It provides empirical evidence of how SHRM responds to welfare‐to‐work programs, informs the development of social policy relevant to disability employment and adopts the notion of institutional fit as a way of explaining how government incentives influence HRM diversity strategies.